The Role of the Chief Digital Officer-a (CDO) and the Chief Information Officer (CIO) in Information System Analysis - Ivanišević, Rajko (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2023)
New discoveries in the field of technology have created a space between the ways in which organizations function and the potential ways in which they function. Recent events have accelerated the need to solve the given problem. All this opens new possibilities in the fields of information systems and digital transformation. With the progress and change in the way the organization functions, there are new requirements in the mentioned areas, but also in the area of ??the staff itself. Chief Digital Officer - CDO (Chief Digital Information Officer - CDIO), a newer position, and Chief Information Officer - CIO are one of the key positions in information technology and digital transformation of the organization. The subject of the research is the analysis of the given roles, their potential inconsistencies, as well as their connection with the information system. Based on the identified works, a systematic review of the literature was performed. The research found that the CDO is more responsible for converting the "traditional" way of doing business into the digital way of doing business, while the CIO is more responsible for the implementation in the field of information technology. Some organizations prefer to expand the activities of the CIO in exchange for hiring a CDO. The field of work research can be a potential topic for further research due to the topicality of the topic itself, as well as the process of digital transformation in which we are currently.